Examining Adaptive Leadership in Business via Literature Review and Bibliometric Analysis - Udin, Udin; Udchachone, Sarinthree; Zumitzavan, Vissanu; Chien, Ng Wei (Pandawan, 2026)
In today’s rapidly changing world, characterized by technological disruption and socio-political complexity, traditional leadership models often prove insufficient. Adaptive leadership provides a flexible approach that enables people to address adaptive challenges through learning, resilience, and systemic change. Despite growing scholarly interest, research on adaptive leadership remains fragmented and lacks strong empirical support. Systematic Literature Review (SLR) and bibliometric analysis of 126 peer-reviewed articles published between 2010 and May 2025 from the Scopus database were employed to address these gaps. Findings reveal a significant rise in publications after 2020, largely influenced by the Covid-19 pandemic and accelerated organizational transformation. Using VOSviewer, the bibliometric analysis identifies influential authors such as R.A. Anderson and D.E. Bailey, leading institutions including Duke University and the University of North Carolina, and prominent publication outlets like California Management Review. Thematic mapping shows a shift from crisis leadership and healthcare to digital agility, emotional intelligence, and psychosocial resilience. This study strengthens the theoretical foundation of adaptive leadership by synthesizing its core competencies, including system diagnosis, distress regulation, and inclusive problem-solving, and demonstrates its practical relevance across sectors. In doing so, it supports global development goals, including SDGs 3 (Good Health and Well-being), SDGs 4 (Quality Education), SDGs 8 (Decent Work and Economic Growth), SDGs 9 (Industry, Innovation, and Infrastructure), and SDGs 16 (Peace, Justice, and Strong Institutions), positioning adaptive leadership as a key driver of sustainable organizational and societal transformation.